1996
DOI: 10.1046/j.1365-2249.1996.d01-723.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of soluble CD14 in serum of patients with acute Plasmodium falciparum malaria

Abstract: Serum sCD14, tumour necrosis factor‐alpha (TNF‐α), IL‐6, and endotoxin were analysed in 45 patients with complicated malaria, in 14 patients with Gram‐negative septicaemia and in 24 healthy subjects by ELISA. Malaria patients with renal failure (n=16) had higher levels than patients without renal failure (n=29) (8116+1440 μg/lversus 9453+1017 μg/lP<0.05) and both had higher levels than patients with septicaemia (6155+1635μg/l) and normal subjects (2776+747 μg/l). A significant correlation between sCD14 and IL‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
19
1
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 37 publications
4
19
1
2
Order By: Relevance
“…Consistent with these findings, CD14 knockout mice were found to be at least 10-fold more resistant to LPS-induced shock than wildtype controls (13). In addition, inflammatory infectious diseases such as atopic dermatitis (14), HIV infection (15), and malaria (16), as well as extensive tissue damage in polytrauma and severe burns (17), are marked by elevated sCD14 in the circulation.…”
mentioning
confidence: 61%
“…Consistent with these findings, CD14 knockout mice were found to be at least 10-fold more resistant to LPS-induced shock than wildtype controls (13). In addition, inflammatory infectious diseases such as atopic dermatitis (14), HIV infection (15), and malaria (16), as well as extensive tissue damage in polytrauma and severe burns (17), are marked by elevated sCD14 in the circulation.…”
mentioning
confidence: 61%
“…Similarly, experimental manipulation of circulating levels of this cytokine in mice by injection of recombinant TGF-β1 or via antibody neutralization indicated that high early or low late TGF-β1 levels were associated with uncontrolled parasitemia and increased pathology (Tsutsui andKamiyama, 1999 andreviewed in Omer et al, 2000). Two studies of natural infection in patients in Gabon (Perkins et al, 2000) and Thailand (Wenisch et al, 1995) and one study of experimental human infection (Walther et al, 2005 andWalther et al, 2006) corroborate these animal studies. Specifically, severe late-stage infection was associated with significantly reduced serum levels of TGF-β1 (7.6 pg/ml, Perkins et al, 2000;14 pg/ml, Wenisch et al, 1995) relative to levels in healthy controls (16 pg/ml, Perkins et al, 2000;63 pg/ml, Wenisch et al, 1995), suggesting that uncontrolled immunopathology exacerbated clinical disease.…”
Section: Introductionmentioning
confidence: 69%
“…3E). These results are interpreted as strong evidence that, in MC, cytokine induction by R-form LPS and lipid A is independent of CD14 under physiological conditions.Enhanced levels of sCD14 render MC responsive to S-form LPS sCD14 levels are strongly up-regulated under inflammatory conditions in both humans and mice [37][38][39][40][41][42][43][44]. Therefore, we investigated also the effects of high concentrations of sCD14 (4 lg/mL recombinant sCD14) on the IL-6 production of MC in response to different amounts of Re-form and S-form LPS (Fig.…”
mentioning
confidence: 99%